2004
DOI: 10.2320/matertrans.45.968
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sulfate Ions on Conversion of Fe(OH)<SUB>3</SUB> Gel to &beta;-FeOOH and &alpha;-Fe<SUB>2</SUB>O<SUB>3</SUB>

Abstract: Powder X-ray diffraction (XRD), transmission electron microscopy (TEM), and chemical analyses were used for characterizing the effect of sulfate ions on the conversion rate of condensed Fe(OH) 3 gel, prepared from FeCl 3 and NaOH solution, to -FeOOH and -Fe 2 O 3 particles by aging at 100 C. Fine particles and supernatant solution were sampled from the aged suspensions containing colloidal particles. XRD profiles and TEM observation showed that -FeOOH was formed from the gel and subsequently converted into -Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Some elements have been found to strongly influence the formation, structure, and morphology of the -FeOOH andFe 2 O 3 particles in aqueous solution systems. [5][6][7] However, further experimental studies about the effects of cations and anions on the formation of the corrosion products are essential for the investigation of the corrosion processes. Silicon (Si) is one of the most important elements of steel and often used as an alloying element so as to improve their corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Some elements have been found to strongly influence the formation, structure, and morphology of the -FeOOH andFe 2 O 3 particles in aqueous solution systems. [5][6][7] However, further experimental studies about the effects of cations and anions on the formation of the corrosion products are essential for the investigation of the corrosion processes. Silicon (Si) is one of the most important elements of steel and often used as an alloying element so as to improve their corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The method to prepare the corrosion product particle samples was fundamentally identical to the previous one [5,6]. 5.4 molL −1 of sodium hydrate solution was added to the same volume of 2.0 molL −1 ferric chloride solution containing 0.05 molL −1 of silicate ion or 0.30 molL −1 of sulfate ion, and the reaction solution was agitated for more than 10 min.…”
Section: Experimental a Preparation Of Powder Samplesmentioning
confidence: 99%
“…In case of coexistence of chloride ions in the solution containing ferric ions, akaganeite β-FeOOH is known to be formed by hydrolysis of ferric species and the precipitates transformed finally into hematite α-Fe 2 O 3 by thermohydrolysis [1,2]. Recently, effects of cations or anions on the formation of akaganeite and its conversion to hematite have been focused and investigated [3][4][5][6]. The results indicated that some elements strongly influence the reaction rate, formation and morphology of final products in aqueous solution systems.…”
Section: Introductionmentioning
confidence: 99%
“…13,14) It is reported that some elements strongly affect the formation and atomic-scale structures of ferric oxyhydroxides. [15][16][17][18][19][20][21][22][23] Therefore, the influence of cations and anions on the atomic-scale structures of ferric oxyhydroxides formed by iron-based alloys and steel under various environments are strongly required in order to understand the relation between the atomic-scale structures and corrosion process.…”
Section: Introductionmentioning
confidence: 99%